UPAYA PENCEGAHAN DAN DETEKSI KANKER PAYUDARA MELALUI SADARI (PEMERIKSAAN PAYUDARA SENDIRI) - Lestari, Indah; Saudah & Catur Prasastia Lukita Dewi, Noer (JURNAL KEPERAWATAN BINA SEHAT, 2018)
Breast cancer International Agency for Research on Cancer (IARC) is ranked first in the worlds highest new case of 43.3%. Based on Pathological Based Registration (2017) at Indonesia, breast cancer ranks first with a relative frequency of 18.6%. More than 80% of cases are found being at an advanced stage, besides that 60-70% of breast cancer treatment seekers are in an advanced stage so that treatment efforts are difficult. Therefore, it needs an understanding of prevention efforts and early diagnosis so thatpatient discovery can be done at an early stage so that it can reduce deaths from breast cancer. ScreeningBreast cancer is an examination or attempt to find abnormalities that lead to breast cancer to someone or group of people who have no complaints. Early attempts to screen for breast cancer is with BSE. BSE training was given to the DPW mother of the Ministry of Religion, Mojokerto Regency, 41 people, using the lecture and video screening method, the BSE simulation, the provision of modules and the BSE leaflet. Effective counseling to increase participants knowledge from the results of the paired sample t-test, seen the mean value of differences in knowledge before extension and after counseling amounted to 2.92 with a standard deviation of 15.79. Statistical test results obtained p-value = 0.035